INTEGRATIVE VALUES OF SUFISM AND NATIONALISM WITHIN SANTRI COMMUNITIES AT PONDOK PESANTREN DAARUL ULUM WAL ḤIKAM YOGYAKARTA (LEADERSHIP AND CHARACTER BUILDING ANALYSIS) - Shofiyana Nadia Fairuz (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2018)
National identity crisis emerged in the country; many pesantren understand Sufism textually, and the need to dialogue Sufism in the national context. The Pesantren of Pesantren Daarul Ulum wal Ḥikam Yogyakarta prepared future leaders with high moral values through the implementation of Sufism and nationalism education in an implementative way through a humanist approach. The researcher employs qualitative method for the field research. Data collection techniques are observation, interview anddocumentation. The data gained then is analyzed through data reduction, data presentationand conclusion making. The validity test of the research data used triangulation techniques and sources. The results showed that, Sufism values are implanted at boarding Daarul Ulumwal Hikam through several methods: (1) role models, (2) spiritual training with phases of Takhalli, Tahalli, Tajalli, and (3) story telling. The values of Sufism include: sincerity,repentance, khauf and raja', zuhud, faqir, patience, ridha, muraqabah. The sufism at thispesantren followed Sunni Sufism based on Ahlussunah wal Jama'ah. Nationalism valuesare inculcated through the following methods: (1) knowing the good, (2) loving the good ,(3) desiring the good. Nationalism values include religious, tolerance, hard work, independent, democratic, patriotism, national spirit, communicative, peace loving, care forthe environment and responsibility based on Pancasila and the 1945 Constitution. The formation of leadership character is done by integrating the values of Sufism and nationalism in teaching and learning activities, pesantren culture and self-development so that the following characters emerge: theocentric, voluntary in serving, wisdom (faṭanah), simplicity, independence, altruism, sincerity, nationalism, responsibility (amanah), rolemodeling, moderate, visionary. The synergy of the values of Sufism and nationalism was applied through the concepts and processes of education that were organized by the pesantren. The synergy produced the values of Sufism which was nuanced by nationalism and created a new educational model namely Sufism-Nationalism Education .